A Survey on Patient Satisfaction with Perioperative Anesthesia Care in a Tertiary Care Centre - Gauchan, Sabin; Thapa, Chitra; Bhusal, Srijana; Bimali, Sneha (Nepal Medical College Journal, 2023)
Patient satisfaction is a well-established indicator of quality of medical care and an important tool for improving standards of health care. This study aimed to find the mean patient satisfaction with perioperative anaesthesia care they received. A descriptive cross-sectional study was conducted at post-anesthesia care unit (PACU) of a tertiary care centre from January 2022 to July 2022 after ethical approval from the Institutional Review Committee (Reference No.: 045-078/079). All the patients who underwent emergency and elective surgery under central neuraxial blockade, peripheral nerve blockade or general anesthesia with intubation were assessed using a 10-item predesigned questionnaire. A total of 330 patients completed the questionnaire. In our patients the interpersonal and emotional aspects related to patient satisfaction was similar with all the three types of anesthesia. But patients who received general anesthesia were less satisfied with postoperative pain and postoperative nausea vomiting management. We found that our patients were satisfied with the perioperative care in terms of interpersonal and emotional aspects. The patients who underwent surgery under general anesthesia were less satisfied in terms of physical aspects such as pain and nausea vomiting as compared to patients who underwent surgery under regional anesthesia.